2011
DOI: 10.2225/vol14-issue2-fulltext-11
|View full text |Cite
|
Sign up to set email alerts
|

New stereoisomeric derivatives of jasmonic acid generated by biotransformation with the fungus Gibberella fujikuroi affect the viability of human cancer cells

Abstract: Background: Several studies have shown that (-)-Jasmonic acid, (+)-7-iso-Jasmonic acid and its methyl ester, methyl jasmonate, have anti-cancer activity in vitro and in vivo, exhibiting selective cytotoxicity towards cancer cells. The degree of activity of these molecules is strongly related to their stereochemistry. The biotransformation of known compounds, natural or synthesized, related to interesting biological activities, generates new molecules displaying new improved properties compared with the origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The principle applied involves the ability of metabolically active cells being able to convert the dye to water-insoluble dark blue formazan and in the process reducing cleavage of the tetrazolium ring [13]. MTT was dissolved in Phosphate Buffer Solution to produce a 5 mg/mL solution; it was then filtered using Millex Syringe Driven Filter Unit (0.22 μm) before being combined with media to produce 10 mL MTT-media solution (20% MTT : 80% media).…”
Section: Sample Preparation and Mtt Antiproliferative Assaymentioning
confidence: 99%
“…The principle applied involves the ability of metabolically active cells being able to convert the dye to water-insoluble dark blue formazan and in the process reducing cleavage of the tetrazolium ring [13]. MTT was dissolved in Phosphate Buffer Solution to produce a 5 mg/mL solution; it was then filtered using Millex Syringe Driven Filter Unit (0.22 μm) before being combined with media to produce 10 mL MTT-media solution (20% MTT : 80% media).…”
Section: Sample Preparation and Mtt Antiproliferative Assaymentioning
confidence: 99%
“…The apoptosis evocated by this new molecule appeared, at least in part, to be associated with an increase in reactive oxygen species (ROS) production . A study indicated that three JA derivatives obtained by biotransformation were specifically active on several types of cancer cells . One of the α‐haloenone analogs, methyl 5‐chloro‐4,5‐didehydrojasmonate or J7, a methyl jasmonate (MeJA) analog, induced significant apoptosis by activation of caspase‐3 and the mitochondrial apoptosis signaling pathway in Hep3B cells .…”
Section: Biological Activities Of Ja Derivativesmentioning
confidence: 99%
“…The apoptosis evocated by this new molecule appeared to associated with an increase in reactive oxygen species (ROS) production (Reinbothe et al, 2009). A study indicated that three JA derivatives obtained by biotransformation were specifically active on several types of cancer cells (Carvajal et al, 2011(Carvajal et al, , 2012(Carvajal et al, , 2013.…”
Section: Anticancer Activitymentioning
confidence: 99%